Analysis of the Development of Pangururan Waterfront City and Its Implications for Tourism in Samosir Regency - Hotler Tamba; Cut Nuraini; Abdi Sugiarto (Journal of Research in Social Science and Humanities, 2026)
This study examines the development of Waterfront City Pangururan and its contribution to tourism enhancement in Samosir Regency. The research aims to identify how spatial arrangement quality, accessibility, and landscape perception influence tourist experience and destination attractiveness. A mixed-methods approach was applied by integrating quantitative assessments from 120 tourists with qualitative observations and open-ended responses, supported by SWOT analysis to formulate strategic development directions. Findings indicate that cleanliness, visual aesthetics, and lakeside panoramas are the most prominent strengths of the area, while limitations in public facilities, inconsistent pedestrian paths, and insufficient vegetation remain key challenges. Accessibility is generally perceived as good, yet the lack of activity diversification reduces the appeal on non-weekend days. The study concludes that improving public facilities, enhancing landscape design, diversifying attractions, and strengthening the visual identity of the waterfront are essential to support sustainable destination development. The implications highlight the need for actionable, phased strategies that align with regional tourism priorities and can be implemented to increase tourist satisfaction, length of stay, and economic benefits for local communities.